The Impact of Different Sources of Dietary Nitrate on Blood Pressure and Other Risk Factors for Cardiovascular Diseases in a Representative UK Population. (7th June 2021) - Alzahrani, Hayat; Jackson, Kim; Hobbs, Ditte; Lovegrove, Julie
Abstract: Objectives: To investigate the relationship between dietary nitrate consumption from vegetables (root and green leafy varieties), drinking water and cured meat, and cardiovascular disease (CVD) risk factors in a representative UK population, and determine whether the source (vegetables vs cured meats) impacts on these relationships. Methods: For this analysis, we used data from the UK cross-sectional National Diet and Nutrition Survey (NDNS) years 1–8, which included 3407 men and women aged 19–64 y. Since data available on dietary analysis software for nitrate levels in vegetables and vegetable-based foods is very limited, a comprehensive database was first developed to evaluate the nitrate and nitrite levels in water, vegetables, cured meats and composite dishes to more accurately estimate the dietary nitrate intakes of the participants. The population was then classified into quartiles based on increasing daily nitrate intakes from vegetables (including drinking water) and meats. ANCOVA analysis determined the relationship between the level of nitrate intake from each dietary source with available data on biomarkers of CVD risk (BP, lipid profile, C-reactive protein (CRP), anthropometric measures and glycaemic control). Results: Across increasing quartiles of dietary nitrate intake from vegetables, there were significant differences in systolic ( P = 0.038) and diastolic ( P = 0.014) BP, with significantly lower BP in Q3 than all other quartiles. Furthermore, nitrate intake from vegetables was significantly associated with lower glucose, glycated haemoglobin, CRP and total cholesterol concentrations in Q4 compare to Q1 (p = 0.046, p = 0.01, p = 0.03 and p = 0.04) respectively. In contrast, there were no changes in CVD markers including BP across quartiles of nitrate from meats. Conclusions: Our findings suggest the source of dietary nitrate may play an important role in determining the relationship with BP, with an intake of between 95–130 mg/day from vegetables and drinking water associated with a lower BP. Funding Sources: Hayat was supported by King Saud University (Saudi Arabia).